ANTIBACTERIAL ACTIVITY OF THE Artemisia herba-alba Asso ESSENTIAL OIL (SOUK AHRAS, ALGERIA) AGAINST FOURTEEN BACTERIAL STRAINS - BOUHOUIA, A; MAAZI, M.C; CHEFROUR, A (My University, 2019)
Artemisia herba-alba Asso (Asteraceae) essential oil from Fedj el dib region (Souk Ahras, Algeria) was obtained by hydro-distillation of aerial parts (stems, leaves and flowers) and analyzed by gas chromatography-mass spectrometry (GC/MS) to determine its chemical composition. The main compounds obtained are: 5,6-Dicarbadecaborane (68,33%), 1,5,5-Trimethyl-6- methylene-cyclohexene (7.00%), 4,8,12-Tetradecatrien-1-ol, 5,9,13-trimethyle (5.13%), Bicyclo-[3.1.1]heptane-2-methanol (4.39%) and Cyclo-pentane carboxylic acid 3-methylene (4.19%), Artemisia essential oil also contains Phenol, 2,3,5-trimethyl-(3.15%), Phosphoric acid tribornyl ester (0.61%) and beta.-Pinene (0.29%) and the Thujone (0.16%). Further to the analytic study of essential oil, a biological study was carried out; the purpose of this biological study was to assess the antibacterial properties of Artemisia herba-alba Asso essential oil against fourteen Gram-positive and Gram-negative bacterial strains using disk diffusion method. The results obtained reveal that the Artemisia herba alba Asso essential oil exerts a strong antimicrobial activity against all tested pathogenic bacteria except P. aeruginosa and Proteus vulgaris which were resistant even to the highest concentration of essential